Manajemen Sumber Daya Manusia Hijau (Green HRM): Tren Penting Untuk Mendukung Kinerja Berkelanjutan - Anis Fitria; Anniez Rachmawati Musslifah; Faqih Purnomosidi (Jurnal Riset dan Inovasi Manajemen, 2024)
Amid the issue of increasing environmental damage due to production processes, green resource management is needed to minimize these conditions. Green resource management is a company policy in managing human resources sustainably by involving environmental aspects to preserve nature in company management. The increasing role of sustainable development leads to the implementation of environmental issues into the mission, goals, and policies of companies in all functional areas, including human resource management (HRM). This research is a qualitative descriptive study. Descriptive research is aimed at explaining the concept of implementing Green Human Resources Management (GHRM) as a company strategy in the form of efforts to increase productivity and the company's commitment to maintaining environmental sustainability.